Electrophysiological Characterization of Human Atria: The Understated Role of Temperature - Majumder, Rupamanjari; Mohamed Nazer, Afnan Nabizath; Panfilov, Alexander V.; Bodenschatz, Eberhard; Wang, Yong (Frontiers in Physiology, 2021)
Ambient temperature has a profound influence on cellular electrophysiology through direct control over the gating mechanisms of different ion channels. In the heart, low temperature is known to favour prolongation of the action potential. However, not much is known about the influence of temperature on other important characterisation parameters such as the resting membrane potential (RMP), excitability, morphology and characteristics of the action potential (AP), restitution properties, conduction velocity (CV) of signal propagation, etc. Here we present the first, detailed, systematic in silico study of the electrophysiological characterization of cardiomyocytes from different regions of the normal human atria, based on the effects of ambient temperature (5 - 50°C). We observe that RMP decreases with increasing temperature. At ~ 48°C, the cells lose their excitability. Our studies show that different parts of the atria react differently to the same changes in temperature. In tissue simulations a drop in temperature correlated positively with a decrease in CV, but the decrease was region-dependent, as expected. In this article we show how this heterogeneous response can provide an explanation for the development of a proarrhythmic substrate during mild hypothermia. We use the above concept to propose a treatment strategy for atrial fibrillation that involves severe hypothermia in specific regions of the heart for a duration of only ~ 200 ms.